Konstruksi Maskulinitas pada Era Orde Baru dalam Film Seperti Dendam, Rindu Harus Dibayar Tuntas - Adiwinata, Akbar; Muhid, Abdul; Sutarman, Sutarman; Abdussamad, Zainudin (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Films often represent masculinity as a social construction shaped and legitimized by state power. This study examines how the state produces and regulates various forms of masculinity in the film Seperti Dendam, Rindu Harus Dibayar Tuntas. Rather than portraying masculinity as a single and stable identity, the film challenges state-supported hegemonic masculinity by presenting masculine identities as diverse, fluid, and continuously negotiated within particular socio-political contexts. This research employs a multimodal discourse analysis approach to explore the relationship between state authority, gender ideology, and cinematic representation. The findings indicate that the state reinforces hegemonic masculinity through regulatory practices that reproduce patriarchal values and maintain social hierarchies. At the same time, the film opens spaces of resistance, especially for heterosexual men who do not fully conform to dominant masculine norms, enabling them to renegotiate their social position within the masculine order. Although the film was produced during the Reformasi era while narratively set in the Orde Baru period, it reflects a transitional moment in which masculinity is increasingly understood as contested and unstable. The boundaries of masculinity become more flexible, allowing the emergence of new forms of gender negotiation. This study demonstrates that cinema can critically interrogate state-constructed models of masculinity while offering alternative interpretations of masculine identity in post–Orde Baru Indonesian film.